Colorante avocado - Baltazaca Guaranda, Elizabeth (2017)
In the present researching with the subject: "COLORANTE AVOCADO", a natural dye of the purple cabbage (Brassica oleracea var. Capitata) was obtained, with the purpose of taking advantage of the cultures of the small producers of this vegetable, in addition to making known to the society a new alternative of consumption, its nutritional value and to take advantage directly the purple cabbage (Brassica oleracea var. Capitata), after having realized the process of extraction of the colorant was applied in yogurt and was made by students and teachers of the Agroindustrial Engineering Career, applying a survey of the evaluation of the organoleptic properties, once the information was compiled, a design of order and frequencies was applied in order to determine its acceptability. The soxhlet extraction method was used to obtain the natural pigment in 95% ethyl alcohol, the juice was mixed with the alcohol, then sieved with the aid of canvas cloth by removing all the solids and finally the solution was placed in Soxhlet equipment. With the natural colorant samples, the physicochemical and microbiological analyzes were performed in an accredited laboratory, obtaining the following results: moisture (99.7%), total solids (0.344%), pH (5.69), aerobic mesophiles 10), total coliforms (<10), eschericha coli (<10), molds (<10) and yeasts (<10). Once obtained the results and compared with the norm NTE INEN 2337: 2008 for juices, pulps, concentrates, nectars, fruit and vegetable drinks we can shake that the obtained concentrate can be applied to an alimentary product. In addition, a study was performed comparing attributes between the natural dye applied yogurt and the commercial yogurt, resulting in a greater acceptability of the yogurt submitted to dye application.